Autism-Risk Gene necab2 Regulates Psychomotor and Social Behavior as a Neuronal Modulator of mGluR1 Signaling - Chen, Zexu; Long, Han; Guo, Jianhua; Wang, Yiran; He, Kezhe; Tao, Chenchen; Li, Xiong; Jiang, Keji; Guo, Su; Pi, Yan (Frontiers in Molecular Neuroscience, 2022)
Background De novo deletion of the neuronal calcium-binding protein 2 (NECAB2) locus is associated with idiopathic autism spectrum disorders (ASDs). The in vivo function of NECAB2 in the brain remains largely elusive. Methods We investigated the morphological and behavioral profiles of both necab2 knock-out and overexpression zebrafish models. The expression pattern and molecular role of necab2 were probed through a combination of in vitro and in vivo assays. Results We show that Necab2 is a neuronal specific, cytoplasmic, and membrane-associated protein, abundantly expressed in the telencephalon, habenula, and cerebellum. Necab2 is distributed peri-synaptically in subsets of glutamatergic and GABAergic neurons. CRISPR/Cas9-generated necab2 knock-out zebrafish display normal morphology but exhibit a decrease in locomotor activity and thigmotaxis with impaired social interaction only in males. Conversely, necab2 overexpression yields behavioral phenotypes opposite to the loss-of-function. Proteomic profiling uncovers a role of Necab2 in modulating signal transduction of G-protein coupled receptors. Specifically, co-immunoprecipitation, immunofluorescence, and confocal live-cell imaging suggest a complex containing NECAB2 and the metabotropic glutamate receptor 1 (mGluR1). In vivo measurement of phosphatidylinositol 4,5-bisphosphate further substantiates that Necab2 promotes mGluR1 signaling. Conclusions Necab2 regulates psychomotor and social behavior via modulating a signaling cascade downstream of mGluR1.